Foods and Beverages Associated with Smoking Craving in Heated Tobacco Product and Cigarette Smokers: A Cross-sectional Study - Kiho Miyoshi; Yuki Kimura; Misaki Nakahata; Takashi Miyawaki (Tobacco Induced Diseases)
Introduction Certain foods and beverages are associated with smoking craving. However, only few studies have explored the relationship between food or beverage-related and taste-associated smoking craving. In this study, we aimed to identify the types of foods related to smoking craving in Japanese individuals who smoke cigarettes or heated tobacco products (HTPs).